Characterization of the gene for the microbody (glycosomal) triosephosphate isomerase of Trypanosoma brucei. - Swinkels, B W (1986)
To determine how microbody enzymes enter microbodies, we are studying the genes for glycosomal (microbody) enzymes in Trypanosoma brucei. Here we present our results for triosephosphate isomerase (TIM), which is found exclusively in the glycosome. We found a single TIM gene without introns, having one major polyadenylated transcript of 1500 nucleotides with a long untranslated tail of approximately 600 nucleotides. By a novel method, suitable for low abundance transcripts, we demonstrate that TIM mRNA contains the 35-nucleotide leader sequence (mini-exon) also found on several other trypanosome mRNAs. The TIM gene and a DNA segment of at least 6 kbp upstream of the gene are transcribed at an equal rate in isolated nuclei, suggesting that the gene is part of a much larger transcription unit. The predicted protein is of the same size as TIMs from other organisms and shares approximately 50% amino acid homology with other eukaryote TIMs, somewhat less with prokaryote TIMs. Trypanosome TIM is the most basic of all TIMs sequenced thus far. This is, in part, due to the presence of two clusters of positively charged residues in the molecule which may act as a signal for entry into glycosomes.